Relationship Between Work Duration and Work Experience with the Occurrence of Low Back Pain in Online Motorcycle Drivers - Farhah, Putri Dzahabiyyah; Setiorini, Anggi; Graharti, Risti; Saftarina, Fitria (Medula, 2025)
Low Back Pain (LBP) is one of the most prevalent musculoskeletal disorders globally and a leading cause of disability. One of the occupational groups at high risk of LBP is online motorcycle taxi drivers, who spend long hours in a static sitting position while riding. The primary factors contributing to LBP among online motorcycle taxi drivers include long working hours and extended work tenure. This study aims to analyze the relationship between working duration and work tenure with the occurrence of LBP among online motorcycle taxi drivers. Based on various studies, it has been found that working more than 8 hours per day can increase the risk of LBP by up to 3.6 times due to excessive muscle strain and spinal load. Additionally, work tenure exceeding 5 years is associated with a higher risk of LBP due to accumulated physical stress, which can reduce muscle performance and deteriorate overall physical condition. Studies conducted in various cities, such as Makassar, Surabaya, and Padang, have demonstrated a significant relationship between working duration, work tenure, and the incidence of LBP among online motorcycle taxi drivers. Implementing proper work time management and ensuring sufficient rest breaks during riding are crucial steps in reducing the risk of LBP among online motorcycle taxi drivers. Additionally, attention to ergonomic factors in riding posture is essential to minimize the negative impact on musculoskeletal health.